Are food price promotions predictable? The hazard function of supermarket discounts. (9th July 2021) - Lan, Hao; Lloyd, Tim; Morgan, Wyn; Dobson, Paul W.
Abstract: Is the timing of food products going on sale, in the form of temporary price reductions, random or predictable? More specifically, are products more likely to go on sale the longer they remain non‐promoted? We investigate the nature and timing of sales discounts using a large database based on weekly supermarket scanner prices covering 500 products for 137 weeks in the largest seven national retail chains in the UK. Our duration analysis of regular price spells reveals that discounting for a wide range of food products is more likely the longer they remain without a sale. However, critical differences exist between retailers following Hi‐Lo or every‐day‐low‐pricing policies, while the time‐dependent pattern varies considerably across product categories, brand status and discount depth.